Creepy crayon! - Reynolds, Aaron, 1970-; Brown, Peter, 1979- (New York : Simon & Schuster Books for Young Readers, 2022)
When Jasper Rabbit finds a purple crayon willing to do his schoolwork for him, he is elated--at first.
Kirkus Starred, June 2022
Booklist, July 2022
Horn Book, September 2022
2.4
K-3
AD500L
Keywords: Rabbits -- Juvenile fiction; Crayons -- Juvenile fiction; Rabbits -- Fiction; Crayons -- Fiction; Animal fiction